Strategies in E-commerce for Air Products Singapore - Tan, Cindy Lucia Lydiawati (2008)
The challenge to the first incentive is the disability of gas suppliers to drive the technology development, a role that is held by the tool manufacturers. Furthermore, tool manufacturers often have the power of endorsement to the gas used by the customers. We therefore suggested that gas supplier needs to build an alliance with the tool manufacturers to achieve a better position than the competitors.